Prevalence of hypertension and its risk factors among obese adolescents in Yogyakarta, Indonesia - Neti Nurani; Navilah Hidayati; Delvira Anggraini; Nurkharisma Kusumawardani; Retno Palupi-Baroto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2021)
Obesity and overweight are considerable health problems with increasing prevalence among adolescents. In Indonesia, basic health research data from Riskesdas shows an increase in the prevalence of obesity in adolescents aged 13-15 y.o, from 2.6% in 2010 to 6.7% in 2013. This high prevalence of overweightand obesity is related to various factors. This study aimed to determine the factors associated with hypertension and obesity in adolescents. This study was conducted on an overweight population, obese, and super-obese adolescents aged 13-15 year in the Yogyakarta City, Indonesia. Demographic data included the history of breastfeeding, birth weight, gender, history of premature birth, lifestyle, and physical activity were gathered. Anthropometric data included the weight, height, and body mass index (BMI) were also measured and gathered. Hypertension was measured using a manual sphygmomanometer. The relationship was analyzed using Pearson chi-squareand the risk value was demonstrated from the odds ratio (OR). A significant relationship between gender and diastolic hypertension was observed (OR= 2.4; 95%CI = 1.23 – 5.09; p < 0.021). A significant difference related to the number of boy subjects between the 2 groups of overweight and obesity was also observed Compared with girls, boys had a higher risk of obesity (OR = 3.23). Other factors including breastfeeding, history of premature birth, low birth weight, and physical activity were not statistically significant between two groups in this study (p>0.05). in conclusion, there is a relationship between gender and diastolic hypertension incidence among obese adolescents. Boys are more at risk of obesity compared to girls.